2010
DOI: 10.1007/s10903-010-9410-0
|View full text |Cite
|
Sign up to set email alerts
|

Transportation to Clinic: Findings from a Pilot Clinic-Based Survey of Low-Income Suburbanites

Abstract: Health care policymakers have cited transportation barriers as key obstacles to providing health care to low-income suburbanites, particularly because suburbs have become home to a growing number of recent immigrants who are less likely to own cars than their neighbors. In a suburb of New York City, we conducted a pilot survey of low income, largely immigrant clients in four public clinics, to find out how much transportation difficulties limit their access to primary care. Clients were receptive to the opport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
70
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 8 publications
3
70
0
1
Order By: Relevance
“…Nine studies assessed the influence of vehicle access upon access to health care, and all found a positive relationship [2426, 3742]. Vehicle access refers to either owning a car or having access to a car through a family member or friend.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nine studies assessed the influence of vehicle access upon access to health care, and all found a positive relationship [2426, 3742]. Vehicle access refers to either owning a car or having access to a car through a family member or friend.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported that 25 % of patients missed an appointment due to transportation problems [41, 42]. Yang et al [41] studied 183 urban caregivers from Houston and their children’s missed appointments, finding that an inability to find a ride resulted in at least one missed appointment for 25 % of the sample.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Adequate transportation is fundamental to health care utilization. 1418 Individuals report poorer health when transportation problems impede their ability to reach care; individuals who report transportation barriers to care are more likely to be female, poor, less educated, and to belong to a racial/ethnic minority than those who were able to travel to care. 16,19 Most studies that have explored the relationship of transportation access to unmet need for medical care use individual-level measures of transportation (e.g., self-reported transportation barriers).…”
mentioning
confidence: 99%